Intelligent thawing household refrigerator. (25th February 2015) - Wang, Shuqing; Lei, Guibin; Qiu, Xiangru; Li, Canping
Abstract: Quick thawing destroys the taste and some nutrients of frozen foods and their thawing in crisper of normal household refrigerator needs manual operation. Intelligent thawing household refrigerator includes an insulated crisper and several insulated freezers where temperature is controlled respectively by SCM (single-chip microcontroller). They are connected by inlet wind pipes and return wind pipes, which are equipped with solenoid valves and blowers. SCM system controls them and makes cooling capacity of freezers to flow into the crisper slowly. With SCM technology and wind circulation technology, frozen foods thaw out slowly and automatically according to the user's appointment in the freezers and their taste and nutrients are preserved. In addition, owing to design of multiple independent insulation freezers and cooling capacity of freezers to flow into the crisper, intelligent thawing household refrigerator saves energy comparing with normal one. Highlights: Foods thaw out slowly their taste and nutrients preserved. Freezers cooling capacity flows into the crisper, so energy is saved. It is convenient that foods thaw out automatically at user's appointment.